A new species of Celatoblatta cockroach that coincides with the distribution of kauri forests in New Zealand - Morgan-Richards M; Trewick SA (Taylor and Francis Group on behalf of the Royal Society of New Zealand, 2025)
A new species of Blattidae cockroach is described from northern Aotearoa New Zealand. Celatoblatta kauri sp. nov. can be distinguished from similar conspecific species by its distinctive facial markings. The recorded distribution of Celatoblatta kauri sp. nov. matches that of the historic distribution of kauri forest (Agathis australis) in northern New Zealand. Zoobank LSID: urn:lsid:zoobank.org:pub:93794424-1A7B-4CCA-A7A1-A303BCE8EACA.
Keywords: Aotearoa; biodiversity; Blattidae; Celatoblatta; cockroach; Polyzosteriinae